Intrinsic field-effect mobility in thin-film transistor with polycrystalline In2O3 channel based on transfer length method - Takanori Takahashi; Yukiharu Uraoka (Applied Physics Express)
Field-effect mobility ( μ _FE ), calculated using transconductance in thin-film transistors (TFTs) includes error factors from determination of channel width/length and parasitic resistance ( R _s/d ) at source and drain regions. The apparent μ _FE is generally underestimated owing to the drain voltage drop due to R _s/d , which in turn, is caused by a low channel resistance ( R _ch ) in high-mobility channels. This letter describes the extraction of intrinsic μ _FE ( μ _FEi ) in TFTs with polycrystalline In _2 O _3 channels by separating R _s/d and R _ch , based on the transfer length method. Using the proposed methodology, we obtained a high μ _FEi (>100 cm ^2 Vs ^−1 ) from TFT.